Avifauna of Amistosa Biological Corridor, Puntarenas, Costa Rica (UNED Research Journal, 2021)
Introduction: Birds are particularly susceptible to habitat fragmentation, which endangers local populations and even whole species. Vegetation corridors are a useful tool to connect protected areas and to reduce the effects of fragmentation. Objectives: To characterize the birdlife in a Costa Rican wildlife corridor. Methods: Between February and June, I sampled transects in several sections of the corridor and recorded bid species between 5:30 a.m. and 3:30 p.m. To complement the species list, I used the platform ebird and a list provided by local bird-watching organizations. Results: The corridor is used by at least 418 species from 60 families. The three most abundant were Tyrannidae, Parulidae and Thraupidae. Of them, 218 species are associated with open habitats, 157 with forested areas, and 41 with aquatic habitats. There are eight trophic guilds. A total of 313 species are residents, 61 migratory, and 27 have both, resident and migratory populations; 19 species are residents with some type of endemism, and one is endemic to the country; 50 present altitudinal migrations. Ten species are near threatened, 7 vulnerable and one species endangered in the UICN list; 215 species have decreasing populations, 114 species stable and 57 have a growing population. Conclusion: The birds of Amistosa include hundreds of species and many ecological types, highlighting the importance of this tropical biological corridor.
Keywords: birds; connectivity; declining populations; diversity; forest